A survey on the usage patterns of the College of Human Kinetics Library users - Santos, John Reginald L. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
Information is a very important part of people's lives. Through information people learn and express new ideas by making it available for the world to see. Information, no matter how minute, can have a tremendous impact when utilized properly and wisely.